MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE EXPILICIT INTRUCTION PADA SISWA KELAS III MI MIFTAHUL JANNAH CIJANTUNG - NURHAYATI NURHAYATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study is an attempt to determine the improvement of mathematics learning outcomes in third grade students of MI Miftahul Jannah, East Jakarta by using the Explicit Instruction method. This research is Classroom Action Research (CAR), which consists of two cycles and each cycle includes planning, implementation, observation, and reflection. The instruments used are test instruments in the form of learning outcomes tests and non-test instruments in the form of observation sheets, field notes and interview guidelines. From the results of the study showed that the use of the Explicit Instruction learning method was very effective on student learning outcomes which were applied in learning mathematics, this was evidenced by an increase in student learning outcomes in mathematics from cycle I to cycle II. In the first cycle there were only 15 students (57.6%) who finished, while the students who scored below 67 or those who had not finished were 11 students (42.3%). The average value of student learning outcomes in the first cycle is 67.3. In Cycle II, students who completed increased to 24 students (92.3%), while students who scored below 67 or students who had not completed as many as 2 students (7.6%), and the average value of student learning outcomes increased to reach 82.3. Student learning activities also increased, from 64% in the first cycle to 84% in the second cycle ABSTRAKPenelitian ini merupakan usaha untuk mengetahui peningkatan hasil belajar matematika pada siswa kelas III MI Miftahul Jannah Jakarta Timur dengan menggunakan metode Explicit Intruction. Penelitian ini adalah Penelitian Tindakan Kelas (PTK), yang terdiri dari dua siklus dan setiap siklus meliputi perencanaan, pelaksanaan, pengamatan, dan refleksi. Instrumen yang digunakan adalah instrumen tes yang berupa tes hasil belajar dan instrumen non tes berupa lembar observasi, catatan lapangan dan pedoman wawancara. Dari hasil penelitian memperlihatkan bahwa penggunaan metode pembelajaran Explicit Intruction sangat efektif terhadap hasil belajar siswa yang diterapkan dalam pembelajaran matematika, hal ini dibuktikan dengan adanya peningkatan hasil belajar matematika siswa dari siklus I ke siklus II. Pada siklus I siswa yang tuntas hanya 15 siswa (57,6%), sedangkan siswa yang memperoleh nilai dibawah 67 atau siswa yang belum tuntas sebanyak 11 siswa (42,3%). Nilai rata-rata hasil belajar siswa siklus I adalah 67,3. Pada Siklus II, siswa yang tuntas meningkat menjadi 24 siswa (92,3%), sedangkan siswa yang memperoleh nilai dibawah 67 atau siswa yang belum tuntas sebanyak 2 siswa (7,6%), dan nilai rata-rata hasil belajar siswa meningkat mencapai 82,3. Aktivitas belajar siswa juga meningkat, dari 64% pada siklus I menjadi 84% pada siklus II